1. Wykonaj mnożenia (prosiłabym bardziej rozpisać)
a) 5(x - 7y + 4 ) =
b) 3x (x - 9y - 11) =
c) 10ab ( 3,4a²b - 2,5ab - 9,3b² - 8a²) =
d) 20az(1,5a - 4,5z + 8az - ¼ ) =
e) 3,5x²y(6x - 8yz - y²x + 12 ) =
f) 2,4xay ( 0,2ay² - 5x²y + 15 - 10x²yz) =

2. Wykonaj mnożenia i przeprowadź redukcie

2

Odpowiedzi

2010-02-19T19:39:36+01:00
A) 5(x - 7y + 4 ) =5x-35y+20
b) 3x (x - 9y - 11) =3x²-27xy-33x
c) 10ab ( 3,4a²b - 2,5ab - 9,3b² - 8a²) =34a³b²-25a²b²-93ab³-80a3b
d) 20az(1,5a - 4,5z + 8az - ¼ ) =30a²z-90az²+160a²z²-5az
e) 3,5x²y(6x - 8yz - y²x + 12 ) =21x³y-28x²y²z-3,5x³y³+42x²y
f) 2,4xay ( 0,2ay² - 5x²y + 15 - 10x²yz) = 0,48xa²y³-12x³ay²+36xay-24x³ay²z
2 2 2
2010-02-19T19:43:31+01:00
1. Wykonaj mnożenia (prosiłabym bardziej rozpisać)
a) 5(x - 7y + 4 ) =
5x+5*(-7y)+4*5=
=5x-35y+20

b) 3x (x - 9y - 11) =
3x*x+ 3x*(-9y)+ 3x*(-11)=
=3x²-27xy-33x

c) 10ab ( 3,4a²b - 2,5ab - 9,3b² - 8a²) =
10ab*3,4a²b +10ab*(-2,5ab)+ 10ab*(-9,3b²)+10ab*(-8a²)=
=34a(do potegi 3)b² -25a²b² -93ab(do potegi 3) -80a(do potegi 3)b

d) 20az(1,5a - 4,5z + 8az - ¼ ) =
20az*1,5a +20az*(-4,5z)+ 20az*8az +20az*(- ¼)=
30a²z -90az² +160a²z² -5az

e) 3,5x²y(6x - 8yz - y²x + 12 ) =
3,5x²y*6x +3,5x²y*(-8yz) +3,5x²y*(-y²x) +3,5x²y*12=
21x(do potegi 3)y -28x²y²z -3,5x(do 3)y(do 3) +42x²y

f) 2,4xay ( 0,2ay² - 5x²y + 15 - 10x²yz) =
2,4xay*0,2ay² +2,4xay*(-5x²y) +2,4xay*15 +2,4xay*(-10x²yz)=
0,48xa²y(do 3) -12x(do 3)ay² +36xay -24x(do 3)ay²z

zad 2.
Nie dodałaś
5 4 5